2022
DOI: 10.1186/s12910-022-00790-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient consent preferences on sharing personal health information during the COVID-19 pandemic: “the more informed we are, the more likely we are to help”

Abstract: Background Rapid ethical access to personal health information (PHI) to support research is extremely important during pandemics, yet little is known regarding patient preferences for consent during such crises. This follow-up study sought to ascertain whether there were differences in consent preferences between pre-pandemic times compared to during Wave 1 of the COVID-19 global pandemic, and to better understand the reasons behind these preferences. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These conclusions included the same themes seen in the reviews, i.e., trust (including conditional trust and transparency), privacy, active engagement of participants, dynamic processes (featuring the possibility of choices over time), education and the raising of awareness regarding the benefits of research (Antommaria et al, 2018; Ballard et al, 2020; Barazzetti et al, 2020; Barnes et al, 2020; Carson et al, 2019; Meka et al, 2021; Nunes Vilaza et al, 2021), not to mention the lack of differences in attitudes between people with mental disorders and those without (Sundby et al, 2018). Remarkably, one study found differences between a pre-pandemic cohort and a pandemic cohort regarding data-sharing willingness, showing that dynamic processes would positively influence engagement and trust (Tosoni et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These conclusions included the same themes seen in the reviews, i.e., trust (including conditional trust and transparency), privacy, active engagement of participants, dynamic processes (featuring the possibility of choices over time), education and the raising of awareness regarding the benefits of research (Antommaria et al, 2018; Ballard et al, 2020; Barazzetti et al, 2020; Barnes et al, 2020; Carson et al, 2019; Meka et al, 2021; Nunes Vilaza et al, 2021), not to mention the lack of differences in attitudes between people with mental disorders and those without (Sundby et al, 2018). Remarkably, one study found differences between a pre-pandemic cohort and a pandemic cohort regarding data-sharing willingness, showing that dynamic processes would positively influence engagement and trust (Tosoni et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of health information in the public health response to COVID-19 provided public exposure to the use of aggregated health data on a scale arguably not seen before. It has been found that patients were more comfortable with the sharing of health information with health-related (non-commercial) organisations during the pandemic than prior to the pandemic, [1] although there are conflicting reports around levels of comfort with the sharing of health information for purposes related to COVID-19. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that patients were more comfortable with the sharing of health information with health-related (non-commercial) organisations during the pandemic than prior to the pandemic, [1] although there are conflicting reports around levels of comfort with the sharing of health information for purposes related to COVID-19. [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, do medical ethics require that they do so? Patients have shown a willingness to share medical information for research purposes and to support population health initiatives 3 . Similarly, many patients would likely be amenable to sharing such information to improve their own care.…”
mentioning
confidence: 99%
“…Patients have shown a willingness to share medical information for research purposes and to support population health initiatives. 3 Similarly, many patients would likely be amenable to sharing such information to improve their own care. Because treatment can only be optimized if the treatment team has all relevant available information, it makes sense for such information to be shared.…”
mentioning
confidence: 99%